Upstream Market Power and Wasteful Retailers*. (18th January 2013) - Peitz, Martin; Shin, Dongsoo
Abstract We provide a novel explanation for the wasteful product disposal by retailers. In our model, after purchasing a quantity of a product from the manufacturer, the retailer exerts a costly effort to sell the product to the final users. The manufacturer's production cost and the outside opportunity associated with it is private information. We show that, when the manufacturer has the upstream market power, the retailer sells all units purchased from the manufacturer. However, when the retailer has the market power, it might deliberately purchase more than it sells to the final users (thus wasting the unsold amount).